2015
DOI: 10.4314/sokjvs.v13i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prevalence of bovine fasciolosis and its direct economic losses (del) due to liver condemnation at Makurdi abattoirs north central Nigeria

Abstract: This study was conducted to report the prevalence of bovine fasciolosis and to estimate the direct economic losses (DEL) from condemnation of liver as a result of detection of lesions of fasciolosis in cattle slaughtered in Makurdi abattoirs. Retrospective data were collected from the abattoir records obtained from Ministry of Agriculture and Natural Resources (MANR) Makurdi, from 2008 to 2012. Direct economic losses were calculated based on a pilot study to determine the average price of liver per kilogram (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…The overall retrospective prevalence of bovine fasciolosis during a ten-year period was 1.46%. Higher five-year bovine fasciolosis burden of 14.6% from condemned livers has been reported at Makurdi abattoirs in Nigeria ( Ejeh et al, 2015 ). Also, a higher 28.0% level of fluke infection has been recorded at an abattoir in northern Portugal/Spain ( Arias et al, 2011 ), and much higher prevalence of 68.0% from the disease has been reported in slaughtered cattle at the Lake Chad ( Jean-Richard et al, 2014 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The overall retrospective prevalence of bovine fasciolosis during a ten-year period was 1.46%. Higher five-year bovine fasciolosis burden of 14.6% from condemned livers has been reported at Makurdi abattoirs in Nigeria ( Ejeh et al, 2015 ). Also, a higher 28.0% level of fluke infection has been recorded at an abattoir in northern Portugal/Spain ( Arias et al, 2011 ), and much higher prevalence of 68.0% from the disease has been reported in slaughtered cattle at the Lake Chad ( Jean-Richard et al, 2014 ).…”
Section: Discussionmentioning
confidence: 96%
“…Kuchai et al (2011) have previously reported similar finding of low prevalence of bovine fasciolosis during dry season among cattle of Ladakh in Egypt. In contrast, high liver condemnations due to fasciolosis have been reported at dry season in Ethiopia and Nigeria, and were attributed to long prepatent period that enhance additional infections with resultant elevated prevalence of patent fasciolosis in the late rainy season, which might occur up to the dry season ( Abdulhakim and Addis, 2012 , Ejeh et al, 2015 ). The seasonal pattern of Fasciola infections represents an increased infection rates in the rainy season than in the dry season in our surveys, as previously reported ( Sissay et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence distribution of bovine fasciolosis is mapped (fig. 1) according to available data published between 1980 and 2016 (Schillhorn van Veen, 1980, Nwosu & Srivastava, 1993; Ngwu et al, 2004; Opara, 2005; Ekwunife & Eneanya, 2006; Adedokun et al, 2008; Umar et al, 2009; Ibironke & Fasina, 2010; Sugun et al, 2010; Gboeloh, 2012; Omoleye, 2012; Odigie & Odigie, 2013; Abraham & Jude, 2014; Ardo et al ., 2014; Magaji et al , 2014; Ngele & Ibe, 2014; Onyeabor, 2014; Yahaya & Tyav, 2014; Ejeh et al, 2015; Elelu et al, 2016). The high prevalence rate from liver condemnation in a 3-year period reported in Lagos State (Ibironke & Fasina, 2010) can be explained by the fact that this State is the commercial nerve centre of Nigeria, with a very large human population, and many cattle from all over the country are often slaughtered at the abattoir.…”
Section: Epidemiology Of Bovine Fasciolosis In Nigeriamentioning
confidence: 99%
“…The second, also free-swimming, cercariae stage of the parasite are released from the snail and get attached to fresh water plants as third stage resting encysted metacercariae. Humans or animals that eat or ingest such plants with encysted metacercariae, or drink water that is contaminated with these cysts, can become infected with the parasite (Ejeh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Animals become infected through consumption of infected or contaminated feed, water and pasture (Magaji et al, 2014;Ejeh et al, 2015). Adult fasciola flukes living in the bile duct release eggs into the intestine, which are then passed through the host's stool during defaecation into still water.…”
Section: Introductionmentioning
confidence: 99%